Guidelines for the Enhancement of Famers’ Potential of Sustainable Quality of Life - Boonwises, Supoj; Lapchit, Siriphat (KASEM BUNDIT JOURNAL, 2018)
The main objectives of this research were to outline problems faced by rice farmers in lower northeastern Thailand as well as guidelines for enhancing their potential of sustainable quality of life.. This qualitative research was based on information from field trips and interviews of 25 farmers, local intelligent people and agricultural officers. The final information acquired was then tended to 17 scholars for consideration and comments. It was revealed that farmers in lower northeastern Thailand encountered 5 important problems as follows: Production factors, internal problems, external problems, natural factors and public policy. In order to enhance the formers’ potential for a sustainable quality of life, the following are proposed: Farm knowledge enhancement (soil, water, cultivated area management, seed selection, and animal husbandry); cooperation among scholars and villagers; establishment of a cooperative in line with Sufficiency Economy Philosophy; application of traditional life style to create values; preservation of farming as an occupation; research and development of rice varieties; agricultural Thai rice marketing; and savings and capital management.